Yttrium-stabilized zirconia powder with high flowability and high apparent density as well as preparation method and application of yttrium-stabilized zirconia powder
By combining gel injection molding and spray granulation processes, a high spherical and high flowability yttrium stable zirconia spray powder was prepared, which solved the problem of insufficient loose density and fluidity of the existing powder, and significantly improved the quality and performance of the coating.
Patent Information
- Application Number
- CN202411948242.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
The existing yttrium stable zirconia spray powder has low loose density and fluidity, which affects the stacking capacity during thermal spraying, the density and corrosion resistance of the coating.
The process of combining gel injection molding and spray granulation is adopted to uniformly atomize the yttrium stabilized zirconia slurry by spraying, and cure it in an oily medium to form spherical particles with high spherical shapes. Then, it is filtered, dried and sintered to improve the loose density and fluidity of the powder.
It significantly improves the loose density and fluidity of the yttrium-stable zirconia spray powder, improves the hollowing problem inside the particles, and improves the density and corrosion resistance of the coating.
Smart Images

Figure CN119638411A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a yttrium-stabilized zirconia powder preparation technology field, in particular to a yttrium-stabilized zirconia powder with high fluidity and high bulk density and a preparation method and application thereof. Background Art
[0002] Yttrium-stabilized zirconia has the main characteristics of high melting point, low thermal conductivity, good corrosion resistance, ability to match the thermal expansion properties of high-temperature alloys, and excellent high-temperature stability. It has been widely used as a raw material for thermal barrier coatings and high-temperature structural materials, especially as an important material for thermal barrier coatings of aircraft engine turbine blades, which can significantly improve the operating temperature and efficiency of the engine. However, with the development of the aviation industry, the service environment of thermal barrier coatings has become increasingly harsh, which has also put forward higher requirements for a series of properties of yttrium-stabilized zirconia. Among them, as an important indicator for evaluating powder performance, the improvement of powder bulk density and fluidity is particularly critical.
[0003] Regarding the bulk density and fluidity of the powder, according to relevant research data, the bulk density and fluidity of powder particles with low sphericity are relatively poor, and these properties will have a significant impact on the thermal spraying process. In the thermal spraying process, a lower bulk density will lead to poor stacking ability of the powder, which will affect a series of properties such as the density and corrosion resistance of the coating. However, at present, yttrium-stabilized zirconia spray powder is mostly prepared by melt crushing or agglomeration sintering. Both processes currently have certain problems. The product structure obtained after melt crushing is irregular and the sphericity is very poor. Although the sphericity of the agglomeration sintering process is improved compared to the powder prepared by melt crushing, the interior of the particles will become hollow due to the evaporation of water during the spray granulation process, which is specifically manifested as good fluidity but low bulk density. The bulk density of existing yttrium-stabilized zirconia powders for thermal spraying is generally between 1.7 and 2.3 g / cm 3 The fluidity is generally between 35 and 60 s / 50 g. There are very few reports on yttrium-stabilized zirconia powders with higher bulk density and better fluidity. Summary of the invention
[0004] In view of this, the present invention provides a yttrium-stabilized zirconia powder with high fluidity and high bulk density, and a preparation method and application thereof, so as to improve the sphericity and fluidity of the yttrium-stabilized zirconia spray powder.
[0005] On the one hand, the present invention provides a high-fluidity, high-bulk density yttrium-stabilized zirconia powder, which comprises, by weight: 70-90 parts of yttrium-stabilized zirconia powder, 10-30 parts of organic monomer, 1-3 parts of cross-linking agent, 0.002-0.004 parts of initiator, 0.001-0.003 parts of catalyst, and 1-3 parts of binder.
[0006] On the other hand, the present invention also provides a method for preparing the yttrium-stabilized zirconia powder, comprising:
[0007] a) Raw material mixing: by weight, take 70-90 parts of yttrium-stabilized zirconia powder and 10-30 parts of organic monomer, and mix them evenly;
[0008] b) Raw material refinement: ultrapure water is added to the raw materials after they are evenly mixed, and after they are evenly mixed, sand milling is performed to fully refine the raw materials;
[0009] c) Adding auxiliary materials: taking 1-3 parts of a crosslinking agent, 0.002-0.004 parts of an initiator, 0.001-0.003 parts of a catalyst, and 1-3 parts of a binder by weight, adding them to the refined slurry and stirring them thoroughly to obtain a yttrium-stabilized zirconia slurry;
[0010] d) slurry spheroidization: spraying the yttrium-stabilized zirconia slurry into fine mist particles, i.e., droplets, and then dropping the droplets into kerosene in the form of free fall;
[0011] e) Slurry solidification: After the yttrium-stabilized zirconia slurry droplets are allowed to stand and solidify in kerosene, yttrium-stabilized zirconia spherical particles are formed;
[0012] f) Filtration and drying: separating the yttrium-stabilized zirconia spherical particles from the kerosene by filtering to obtain yttrium-stabilized zirconia spherical powder, and drying the yttrium-stabilized zirconia spherical powder;
[0013] g) Powder sintering: The dried yttrium-stabilized zirconia spherical powder is loaded into a sagger to avoid particle breakage, and then the debinding and sintering processes are performed;
[0014] h) Powder screening: The sintered yttrium-stabilized zirconia spherical powder is screened to obtain a particle product that meets the specification requirements.
[0015] Preferably, the yttrium-stabilized zirconia in a) is selected from fully stable tetragonal fused yttrium-stabilized zirconia powder or high-temperature calcined fully stable phase yttrium-stabilized zirconia powder, and the organic monomer is methacrylamide.
[0016] Preferably, in b), a sand mill is used to sand grind the raw material for 4-8 hours; wherein the sand grinding balls are zirconia ceramic balls;
[0017] b) The amount of ultrapure water added is such that the solid content of the mixed slurry is controlled between 55% and 70%;
[0018] CE64 can also be added as a dispersant in b) to further improve the fluidity of the slurry.
[0019] Preferably, in c), the crosslinking agent is N,N-methylenebisacrylamide, the initiator is ammonium persulfate, the catalyst is N,N,N',N'-tetramethylethylenediamine, the binder is PVA, and the stirring time is within 3-5 minutes.
[0020] Preferably, in d), the slurry is sprayed into fine mist particles using a spray gun, the spray gun pressure is 0.5-1.5 MPa, and the spraying time is less than 15 minutes.
[0021] Preferably, the slurry in e) is allowed to stand and solidify for 30-60 minutes.
[0022] Preferably, in f), the yttrium-stabilized zirconia spherical powder is placed in an oven for drying, and the drying program is set to 50° C. for 2-4 hours, and then the temperature is increased to 105° C. and the drying is continued for 4-6 hours.
[0023] Preferably, the binder removal process in g) is: gradually raising the temperature to 550°C, controlling the heating rate at 1°C / min, and keeping the temperature at this temperature for 3-5 hours; after the binder removal is completed, sintering is performed, and the temperature is further raised to 1300°C at a rate of 5°C / min, and kept at this temperature for 2-5 hours;
[0024] h) The screening is carried out using ultrasonic three-element vibration screen equipment, and after screening, the products with particle sizes between +50μm and -150μm are retained.
[0025] Finally, the present invention also provides the application of the yttrium stabilized zirconia powder in thermal barrier coatings.
[0026] The present invention provides a high-fluidity, high-loose density yttria-stabilized zirconia powder, and a preparation method and application thereof. The method improves the sphericity and fluidity of the yttria-stabilized zirconia spray powder while improving the hollowing phenomenon inside the particles, so that the powder has a higher loose density. Specifically, in this process, the gel injection molding principle and the spray granulation principle are coordinated to make the slurry uniformly atomized in a spray manner and then drip into a receiving medium of the oily raw material to protect the structural integrity of the slurry droplets. Under the action of gravity and buoyancy, the ceramic droplets are able to maintain a high sphericity in the liquid medium, and then slowly solidify and form strength. After filtering, drying, and sintering, the purpose of improving the fluidity and loose density of the yttria-stabilized zirconia spray powder is achieved.
[0027] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0030] Figure 1 An X-ray diffraction spectrum of a high-flowability and high-bulk-density yttrium-stabilized zirconia powder provided in an embodiment of the present invention;
[0031] Figure 2 A surface SEM of a high-fluidity and high-bulk-density yttrium-stabilized zirconia powder provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0032] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are merely examples of methods consistent with some aspects of the present invention as detailed in the appended claims.
[0033] In the prior art, yttrium-stabilized zirconia thermal spray powder is mainly prepared by melt crushing or agglomeration sintering process. However, the product obtained by the melt crushing process has an irregular structure and poor fluidity. Although the agglomeration sintering process can produce products with a spherical structure, the evaporation of water in the spray granulation process will cause the particles to become hollow inside. Although the fluidity is good, the loose density is low.
[0034] The present invention discloses a method for preparing yttrium-stabilized zirconia powder with high fluidity and high bulk density. Yttrium-stabilized zirconia, as a thermal barrier coating material, is widely used on the surface of high-temperature alloy hot end components in the fields of aviation and aerospace. Its function is to increase the working temperature of high-temperature alloy components and extend their service life. The bulk density and fluidity of thermal spraying powder have a significant impact on the thermal spraying process. If the bulk density of the thermal spraying powder is low and the fluidity is poor, large pores will exist between the powder particles, which will affect the fluidity of the powder, resulting in uneven powder feeding, and ultimately affecting the uniformity of the coating. In addition, a lower bulk density may indicate that the powder particles are finer or irregular in shape, which will lead to a slower flying speed of the particles during spraying, insufficient kinetic energy, and affect the bonding strength between the particles and the workpiece surface, which is likely to cause the coating to be loose and have a high porosity, thereby reducing the coating quality.
[0035] To this end, this embodiment uses an innovative preparation process to improve the sphericity and fluidity of yttrium-stabilized zirconia spray powder while improving the hollowing phenomenon inside the particles to make it have a higher bulk density. Specifically, the gel injection molding principle and the spray granulation principle are integrated so that the slurry is evenly atomized in a spray manner and drips into the receiving medium of the oily raw material to protect the structural integrity of the slurry droplets. Under the action of gravity and buoyancy, the ceramic droplets are able to maintain a high sphericity in the liquid medium, and then slowly solidify and form strength. After filtering, drying, and sintering, the purpose of improving the fluidity and bulk density of yttrium-stabilized zirconia spray powder is achieved.
[0036] The present embodiment provides a high-fluidity and high-bulk density yttrium-stabilized zirconia powder, which comprises, by weight: 70-90 parts of yttrium-stabilized zirconia powder, 10-30 parts of organic monomer, 1-3 parts of cross-linking agent, 0.002-0.004 parts of initiator, 0.001-0.003 parts of catalyst, and 1-3 parts of binder.
[0037] This embodiment also provides a method for preparing the above-mentioned high-fluidity and high-bulk density yttrium-stabilized zirconia powder, comprising:
[0038] a) Raw material mixing: by weight, take 70-90 parts of yttrium-stabilized zirconia powder and 10-30 parts of organic monomer, mix well and set aside;
[0039] The yttrium-stabilized zirconia can be selected from fully stable tetragonal fused yttrium-stabilized zirconia powder or high-temperature calcined fully stable phase yttrium-stabilized zirconia powder, and the organic monomer is methacrylamide.
[0040] b) Raw material refinement: Add a certain amount of ultrapure water to the mixed raw materials, mix them evenly and send them into a sand mill. After sand milling, the raw materials are fully refined and set aside.
[0041] The balls used for sand grinding are zirconia ceramic balls. The solid content of the slurry should be controlled between 55-70%. If the fluidity of the slurry is poor, CE64 can be used as a dispersant to improve the fluidity of the slurry. The sand grinding time is 4-8 hours.
[0042] c) Adding auxiliary materials: by weight, add 1-3 parts of crosslinking agent, 0.002-0.004 parts of initiator, 0.001-0.003 parts of catalyst, and 1-3 parts of binder to the sand-milled slurry, stir evenly, and set aside;
[0043] The cross-linking agent is N,N-methylenebisacrylamide, the initiator is ammonium persulfate, the catalyst is N,N,N',N'-tetramethylethylenediamine, the binder is PVA, and the stirring time is within 3-5 minutes.
[0044] d) Slurry spheroidization: The fully stirred yttrium-stabilized zirconia slurry is injected into a spray gun, and the slurry is sprayed into fine mist particles using the spray gun, and then allowed to fall freely into the kerosene.
[0045] The spray gun pressure should be controlled at 0.5-1.5MPa. All slurries must be sprayed through the spray gun within 15 minutes to prevent the flow rate from slowing down due to the curing reaction, which may cause equipment blockage.
[0046] e) Slurry solidification: The yttrium-stabilized zirconia slurry droplets need to be left standing in the kerosene for a period of time so that the slurry can be fully solidified and then form yttrium-stabilized zirconia spherical particles with a certain strength.
[0047] f) Filtration and drying: The yttrium-stabilized zirconia spherical particles are separated from the kerosene by filtering to obtain yttrium-stabilized zirconia spherical powder, and the filtered yttrium-stabilized zirconia spherical powder is placed in an oven to promote the rapid volatilization of kerosene on the particle surface and remove moisture from the spherical powder at the same time.
[0048] The drying process is set at 50°C for 2-4 hours, then the temperature is raised to 105°C and the drying is continued for 4-6 hours.
[0049] g) Powder sintering: The dried spherical powder is gently loaded into a sagger to avoid particle damage. After debinding and sintering processes, yttrium-stabilized zirconia spherical powder is obtained.
[0050] The temperature should be gradually raised to 550℃ during the debinding process, with the heating rate controlled at 1℃ / min, and kept at this temperature for 3-5 hours. After the debinding process is completed, continue to heat up to 1300℃ at a rate of 5℃ / min, and keep at this temperature for 2-5 hours.
[0051] h) Powder screening: The sintered yttrium-stabilized zirconia spherical powder is screened to obtain a particle product that meets the specification requirements. The screening equipment uses an ultrasonic three-element vibrating screen, and after screening, the product with a particle size between +50μm and -150μm is retained.
[0052] The product obtained by the present invention was characterized by X-ray and surface SEM. Figure 1 and 2 As shown, through Figure 1 It can be seen that the crystal structure of the product is mainly tetragonal. Figure 2 This shows that the product has good sphericity and the particle size generally remains between +50μm and -150μm.
[0053] This embodiment cleverly combines gel injection molding with spray granulation. The yttrium-stabilized zirconia slurry is evenly atomized by spraying, and the atomized ceramic slurry droplets are protected in the receiving medium of the oily raw material. Due to the incompatibility between oil and water, the structural integrity of the ceramic slurry droplets is ensured. In the liquid medium, the ceramic droplets are subjected to the dual effects of gravity and buoyancy, maintaining a high sphericity, thereby ensuring the fluidity of the product. Through the principle of gel injection molding, the ceramic droplets slowly solidify and form strength, avoiding the hollowing problem caused by too fast evaporation of water in the traditional spray granulation process, and effectively improving the bulk density of the product.
[0054] The present invention is further explained below in conjunction with specific embodiments, but is not intended to limit the protection scope of the present invention.
[0055] Example 1
[0056] a) Raw material mixing: Take 90 parts of yttrium-stabilized zirconia powder and 10 parts of organic monomer by weight, mix well and set aside;
[0057] b) Raw material refinement: A certain amount of ultrapure water is added to the mixed raw materials, and the solid content of the slurry is controlled at 70%. After mixing evenly, the raw materials are sent to a sand mill. After 8 hours of sand milling, the raw materials are fully refined and set aside.
[0058] c) Addition of auxiliary materials: by weight, take 1 part of crosslinking agent, 0.002 parts of initiator, 0.001 parts of catalyst, and 3 parts of binder, add them to the sand-milled slurry, stir for 5 minutes, and set aside;
[0059] d) Slurry spheroidization: Pour the fully stirred yttrium-stabilized zirconia slurry into the spray gun, use the spray gun to spray the slurry into fine mist particles, and then let it fall freely into the kerosene. The spray gun pressure is controlled at 1.5MPa during spheroidization.
[0060] e) Slurry solidification: The yttrium-stabilized zirconia slurry droplets need to be left standing in kerosene for 60 minutes so that the slurry can be fully solidified and form yttrium-stabilized zirconia spherical particles with a certain strength.
[0061] f) Filtration and drying: The yttrium-stabilized zirconia spherical particles are separated from the kerosene by filtering to obtain the yttrium-stabilized zirconia spherical powder, and the filtered yttrium-stabilized zirconia spherical powder is placed in an oven to promote the rapid volatilization of the kerosene on the particle surface and remove the moisture inside the spherical powder at the same time. The drying process is set at 50°C for 2 hours, then the temperature is raised to 105°C and the drying is continued for 4 hours.
[0062] g) Powder sintering: The dried spherical powder is gently loaded into the sagger to avoid particle damage. After debinding and sintering, yttrium-stabilized zirconia spherical powder is obtained. The debinding process should be gradually heated to 550°C, the heating rate should be controlled at 1°C / minute, and kept at this temperature for 3 hours. After the debinding process is completed, continue to heat to 1300°C at a rate of 5°C / minute and keep at this temperature for 5 hours.
[0063] h) Powder screening: The sintered yttrium-stabilized zirconia spherical powder is screened, and the products with a particle size between +50 μm and -150 μm are retained after screening.
[0064] Example 2
[0065] a) Raw material mixing: Take 85 parts of yttrium-stabilized zirconia powder and 15 parts of organic monomer by weight, mix well and set aside;
[0066] b) Raw material refinement: Add a certain amount of ultrapure water to the mixed raw materials. The solid content of the slurry should be controlled at 65%. After mixing evenly, send it into a sand mill. After 6 hours of sand milling, the raw materials are fully refined and set aside.
[0067] c) Addition of auxiliary materials: by weight, take 1.5 parts of crosslinking agent, 0.003 parts of initiator, 0.003 parts of catalyst, and 2 parts of binder, add them to the sand-milled slurry, stir for 5 minutes, and set aside;
[0068] d) Slurry spheroidization: Pour the fully stirred yttrium-stabilized zirconia slurry into the spray gun, use the spray gun to spray the slurry into fine mist particles, and then let it fall freely into the kerosene. The spray gun pressure should be controlled at 1MPa during spheroidization.
[0069] e) Slurry solidification: The yttrium-stabilized zirconia slurry droplets need to be left standing in kerosene for 50 minutes so that the slurry can be fully solidified and form yttrium-stabilized zirconia spherical particles with a certain strength.
[0070] f) Filtration and drying: The yttrium-stabilized zirconia spherical particles are separated from the kerosene by filtering to obtain the yttrium-stabilized zirconia spherical powder, and the filtered yttrium-stabilized zirconia spherical powder is placed in an oven to promote the rapid volatilization of the kerosene on the particle surface and remove the moisture inside the spherical powder at the same time. The drying process is set at 50°C for 3 hours, and then the temperature is raised to 105°C and the drying is continued for 5 hours.
[0071] g) Powder sintering: The dried spherical powder is gently loaded into the sagger to avoid particle damage. After debinding and sintering, yttrium-stabilized zirconia spherical powder is obtained. The debinding process should be gradually heated to 550°C, the heating rate should be controlled at 1°C / minute, and kept at this temperature for 4 hours. After the debinding process is completed, continue to heat to 1300°C at a rate of 5°C / minute and keep at this temperature for 4 hours.
[0072] h) Powder screening: The sintered yttrium-stabilized zirconia spherical powder is screened, and the products with a particle size between +50 μm and -150 μm are retained after screening.
[0073] Example 3
[0074] a) Raw material mixing: Take 80 parts of yttrium-stabilized zirconia powder and 20 parts of organic monomer by weight, mix well and set aside;
[0075] b) Raw material refinement: Add a certain amount of ultrapure water to the mixed raw materials. The solid content of the slurry should be controlled at 60%. After mixing evenly, send it into a sand mill. After 6 hours of sand milling, the raw materials are fully refined and ready for use.
[0076] c) Addition of auxiliary materials: by weight, take 2 parts of crosslinking agent, 0.004 parts of initiator, 0.002 parts of catalyst, and 2 parts of binder, add them to the sand-milled slurry, stir for 4 minutes, and set aside;
[0077] d) Slurry spheroidization: Pour the fully stirred yttrium-stabilized zirconia slurry into the spray gun, use the spray gun to spray the slurry into fine mist particles, and then let it fall freely into the kerosene. The spray gun pressure should be controlled at 1MPa during spheroidization.
[0078] e) Slurry solidification: The yttrium-stabilized zirconia slurry droplets need to be left standing in kerosene for 40 minutes so that the slurry can be fully solidified and form yttrium-stabilized zirconia spherical particles with a certain strength.
[0079] f) Filtration and drying: The yttrium-stabilized zirconia spherical particles are separated from the kerosene by filtering to obtain the yttrium-stabilized zirconia spherical powder, and the filtered yttrium-stabilized zirconia spherical powder is placed in an oven to promote the rapid volatilization of the kerosene on the particle surface and remove the moisture inside the spherical powder at the same time. The drying process is set at 50°C for 3 hours, and then the temperature is raised to 105°C and the drying is continued for 5 hours.
[0080] g) Powder sintering: The dried spherical powder is gently loaded into the sagger to avoid particle damage. After debinding and sintering, yttrium-stabilized zirconia spherical powder is obtained. The debinding process should be gradually heated to 550°C, the heating rate should be controlled at 1°C / minute, and kept at this temperature for 4 hours. After the debinding process is completed, continue to heat to 1300°C at a rate of 5°C / minute and keep at this temperature for 3 hours.
[0081] h) Powder screening: The sintered yttrium-stabilized zirconia spherical powder is screened, and the products with a particle size between +50 μm and -150 μm are retained after screening.
[0082] Example 4
[0083] a) Raw material mixing: Take 70 parts of yttrium-stabilized zirconia powder and 30 parts of organic monomer by weight, mix well and set aside;
[0084] b) Raw material refinement: Add a certain amount of ultrapure water to the mixed raw materials. The solid content of the slurry should be controlled at 55%. After mixing evenly, send it into a sand mill. After 4 hours of sand milling, the raw materials are fully refined and set aside.
[0085] c) Addition of auxiliary materials: by weight, take 3 parts of crosslinking agent, 0.004 parts of initiator, 0.003 parts of catalyst, and 1 part of binder, add them to the sand-milled slurry, stir for 3 minutes, and set aside;
[0086] d) Slurry spheroidization: Pour the fully stirred yttrium-stabilized zirconia slurry into the spray gun, use the spray gun to spray the slurry into fine mist particles, and then let it fall freely into the kerosene. The spray gun pressure should be controlled at 0.5MPa during spheroidization.
[0087] e) Slurry solidification: The yttrium-stabilized zirconia slurry droplets need to be left standing in kerosene for 30 minutes so that the slurry can be fully solidified and form yttrium-stabilized zirconia spherical particles with a certain strength.
[0088] f) Filtration and drying: The yttrium-stabilized zirconia spherical particles are separated from the kerosene by filtering to obtain the yttrium-stabilized zirconia spherical powder, and the filtered yttrium-stabilized zirconia spherical powder is placed in an oven to promote the rapid volatilization of the kerosene on the particle surface and remove the moisture inside the spherical powder at the same time. The drying process is set at 50°C for 4 hours, and then the temperature is raised to 105°C and the drying is continued for 6 hours.
[0089] g) Powder sintering: The dried spherical powder is gently loaded into the sagger to avoid particle damage. After debinding and sintering, yttrium-stabilized zirconia spherical powder is obtained. The debinding process should be gradually heated to 550°C, the heating rate should be controlled at 1°C / minute, and kept at this temperature for 5 hours. After the debinding process is completed, continue to heat to 1300°C at a rate of 5°C / minute and keep at this temperature for 2 hours.
[0090] h) Powder screening: The sintered yttrium-stabilized zirconia spherical powder is screened, and the products with a particle size between +50 μm and -150 μm are retained after screening.
[0091] As shown in Table 1 below, the performance test comparison between the yttrium-stabilized zirconia spherical powder prepared by the existing melt crushing and agglomeration sintering process and the yttrium-stabilized zirconia spherical powder obtained in the present application shows that the product obtained by the method of the present application has significantly improved bulk density and fluidity.
[0092] Table 1 Performance test table
[0093] Serial number <![CDATA[Bulk density (g / cm 3 )]]> Fluidity(s / 50g) This application product 3.07-3.19 21.79-22.47 Similar products 1.7-2.3 35-60
[0094] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.
[0095] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A high-flowability, high-bulk-density yttria-stabilized zirconia powder, characterized in that: Calculated by weight, the invention comprises: 70-90 parts of yttrium-stabilized zirconia powder, 10-30 parts of organic monomer, 1-3 parts of cross-linking agent, 0.002-0.004 parts of initiator, 0.001-0.003 parts of catalyst and 1-3 parts of binder.
2. The method for preparing the yttrium-stabilized zirconia powder according to claim 1, characterized in that: include: a) Raw material mixing: by weight, take 70-90 parts of yttrium-stabilized zirconia powder and 10-30 parts of organic monomer, and mix them evenly; b) Raw material refinement: ultrapure water is added to the raw materials after they are evenly mixed, and after they are evenly mixed, sand milling is performed to fully refine the raw materials; c) Adding auxiliary materials: taking 1-3 parts of a crosslinking agent, 0.002-0.004 parts of an initiator, 0.001-0.003 parts of a catalyst, and 1-3 parts of a binder by weight, adding them to the refined slurry and stirring them thoroughly to obtain a yttrium-stabilized zirconia slurry; d) slurry spheroidization: spraying the yttrium-stabilized zirconia slurry into fine mist particles, i.e., droplets, and then dropping the droplets into kerosene in the form of free fall; e) Slurry solidification: After the yttrium-stabilized zirconia slurry droplets are allowed to stand and solidify in kerosene, yttrium-stabilized zirconia spherical particles are formed; f) Filtration and drying: separating the yttrium-stabilized zirconia spherical particles from the kerosene by filtering to obtain yttrium-stabilized zirconia spherical powder, and drying the yttrium-stabilized zirconia spherical powder; g) Powder sintering: The dried yttrium-stabilized zirconia spherical powder is loaded into a sagger to avoid particle breakage, and then the debinding and sintering processes are performed; h) Powder screening: The sintered yttrium-stabilized zirconia spherical powder is screened to obtain a particle product that meets the specification requirements.
3. The method for preparing yttrium-stabilized zirconia powder according to claim 2, characterized in that: a) The yttrium-stabilized zirconia is selected from fully stable tetragonal fused yttrium-stabilized zirconia powder or high-temperature calcined fully stable phase yttrium-stabilized zirconia powder, and the organic monomer is methacrylamide.
4. The method for preparing yttrium-stabilized zirconia powder according to claim 2, characterized in that: b) sand milling the raw material for 4-8 hours; wherein the sand milling balls are zirconia ceramic balls; b) The amount of ultrapure water added is such that the solid content of the mixed slurry is controlled between 55% and 70%; CE64 can also be added as a dispersant in b) to further improve the fluidity of the slurry.
5. The method for preparing yttrium-stabilized zirconia powder according to claim 2, characterized in that: c) wherein the crosslinking agent is N,N-methylenebisacrylamide, the initiator is ammonium persulfate, the catalyst is N,N,N',N'-tetramethylethylenediamine, the binder is PVA, and the stirring time is within 3-5 minutes.
6. The method for preparing yttrium-stabilized zirconia powder according to claim 2, characterized in that: d) The slurry is sprayed into fine mist particles by using a spray gun, the spray gun pressure is 0.5-1.5Mpa, and the spraying time is less than 15 minutes.
7. The method for preparing yttrium-stabilized zirconia powder according to claim 2, characterized in that: The curing time of the slurry in e) is 30-60 minutes.
8. The method for preparing yttrium-stabilized zirconia powder according to claim 2, characterized in that: f) placing the yttrium stabilized zirconia spherical powder in an oven for drying, the drying program is set at 50° C., after 2-4 hours, the temperature is raised to 105° C., and drying is continued for 4-6 hours.
9. The method for preparing yttrium-stabilized zirconia powder according to claim 2, characterized in that: g) The debinding process is as follows: gradually increase the temperature to 550°C, control the heating rate at 1°C / min, and keep it at this temperature for 3-5 hours; after the debinding is completed, sintering is performed, and the temperature is continued to be increased to 1300°C at a rate of 5°C / min, and kept at this temperature for 2-5 hours; h) The screening is carried out using ultrasonic three-element vibration screen equipment, and after screening, the products with particle sizes between +50μm and -150μm are retained.
10. The use of the yttrium-stabilized zirconia powder according to claim 1, characterized in that: The powder is applied to thermal barrier coatings.